Time value of housing: the effect of lease decay on HDB resale prices - CHONG, BENEDICT NICHOLAS (2017)
The aim of this paper is to investigate the effects of remaining lease on the resale housing market. In this paper, we test whether there exists a relationship between remaining lease and public housing price (HDB flats) and to what extent the location of these HDB flats will affect the resale price as compared to our baseline. This paper focuses on examining the resale public housing price in Singapore using the hedonic pricing model, while controlling for various lease conditions such as number of rooms and floor area of the HDB flats. Our main finding in this paper is that resale prices do reflect a decreasing trend as the length of remaining lease decreases. In particular, a decrease in remaining lease by a single year will decrease the monetary value of the HDB flats by SGD 3,917 on average. We have also notice that location of the HDB flats do influence the resale housing price where flats nearer to Town add positive values while flats further away from Town impose a negative value relative to our baseline location.